Rentabilidad de la exportadora de Cacao Babahoyoexport S. A. en los periodos 2020 y 2021. - Ochoa Murillo, Andy Roberto (2023)
The profitability of a cocoa exporter depends on several factors, such as the selling price of the cocoa, production costs and overheads. To increase profitability, companies must find ways to reduce production costs, improve cocoa quality, and increase sales. The following case study is entitled "Profitability of the cocoa exporter Babahoyoexport s.a. in the periods 2020 and 2021" whose main purpose is to publicize the finances of the aforementioned company using financial ratios in the economic statements presented by the organization, together with the obstacles that it encountered during the period of the health emergency using the most appropriate research methods to achieve the outlined objectives, these investigative methods were descriptive-deductive, which were used to analyze the information obtained in various platforms, the lines of research used were Administrative, Tax, Financial Management, Audit and Control as main line; and the research sub-line: Financial, Tax and Social Commitment Management.